A service-oriented cloud modeling method and process - Chee-Yang Song; Eun-Sook Cho (Institute of Advanced Engineering and Science, 2020)
The transition of software development from web to cloud has been accelerated. The development of cloud services requires a modeling method that reflects the characteristics of cloud including personalized service, resource sharing service, grouped and distributed services, and cross-platform operability. This study aimed to suggest a method of developing UML-based cloud services suitable for the characteristics of cloud services. A cloud service metamodel was defined using cloud applications’ characteristic modeling elements, and after that, how these cloud modeling elements are expressed into UML modeling elements was defined with an integrated metamodel between cloud and UML. By applying this hierarchical cloud metamodel, an MDA and MVC-based service-oriented cloud modeling process was established. By doing so, it will be possible to easily design services (applications) and solutions that are suitable for cloud computing environments, and in particular, to create hierarchical reuse models by the level of the abstraction of model-driven development.